Polylactic Acid Implant for Cranioplasty with 3-dimensional Printing Customization: A Case Report - Apriawan, Tedy; Permana, Khrisna Rangga; Darlan, Ditto; Arifianto, Muhammad Reza; Fitra, Fitra; Alfauzi, Asra; Bajamal, Abdul Hafid (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Cranioplasty is aimed to restore the structure and function of the lost portion of the skull defect. Many materials can be used for cranioplasty, such as the bones of the patient (autograft), the bones of other patients (allograft), bones of animals (xenograft), or synthetic materials such as acrylic or titanium mesh. These materials are quite expensive and sometimes require complex processes. Manual shaping of material for cranioplasty is also quite time-consuming and prone to cause esthetic dissatisfaction. The author will discuss the case of using polylactic acid (PLA) implant with 3-dimensional (3D) printing customization as a cheap and accurate cosmetic solution for cranioplasty procedures. CASE REPORT: We report 2 cases of skull defect underwent cranioplasty. The first case, female, 20-year-old, had a history of severe traumatic brain injury (TBI) and epidural hematoma. She underwent decompression craniotomy on the left frontotemporoparietal region of her skull. The second case, male, 46-year-old, had a history of spontaneous intracerebral hemorrhage due to arteriovenous malformation (AVM). He underwent decompression craniotomy on the right frontotemporoparietal region of her skull. Both the data of computerized tomography (CT) scan were reconstructed to get 3D model of skull defect. Prosthesis was made by 3D printer accordingly using PLA as material. There was no complication reported postoperatively and cosmetic satisfaction was obtained on both cases. CONCLUSION: The use of PLA implant with 3D printing customization was proved to be cost-effective and good cosmetic satisfaction with no complication reported following cranioplasty procedure.